Prevalence and risk factors for Pulmonary Embolism (PE) and Deep Vein Thrombosis (DVT) during Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) - Buklioska Ilievska, Daniela; Trajkovska, Ivana; Kuzmanovska Dimitrovska, Melina (VM Media SP. zo.o VM Group SK, 2020)
Introduction: COPD patients are at high risk for PE and DVT due to immobility, inflammation, comorbidities. Prevalence of PE during AECOPD is uncertain and often under-diagnosed. Material and methods: Single-center, prospective, an observational trial of 100 hospitalized patients with AECOPD, diagnosed according to GOLD criteria, 40–75 years, stratified according to airflow limitation (I–IV), divided into subgroups (PE-diagnosed/non-PE and with known/ undetermined exacerbation etiology). Investigations: clinical risk assessment, electrocardiogram (ECG), laboratory, spirometry, gas-analysis, D-dimer (DD), chest X-ray, thoracic ultrasonography (TUS), Doppler-ultrasonography of deep-veins of lower-extremities (DULE). Patients with high DD and DVT or high DD and abnormal TUS underwent computed-tomography pulmonary-angiography (CTPA). Results: PE was diagnosed in 26 (26.0%), DVT in 5 (5.0%) of hospitalized AECOPD patients. There was a positive correlation between COPD-severity and PE. Frequencies of PE in GOLD-stages I, IV, were 0 (0.0%), 3 (11.5%), 8 (30.7%), 15 (57.7%) respectively. Patients with pleuritic chest-pain, TUS abnormality, phlebitis and high DD were more likely to develop PE. Localization was subsegmental in 9 (34.6%), in one of the main pulmonary arteries 7 (26.9%), lobar and interlobar arteries in 10 (38.5%). DD was significantly higher among patients with PE than those without (3.34 ± 1.1 μg/mL vs. 2.2 ± 0.8μg/mL, P < 0.0001). There was positive correlation between the presence of PE and elevated DD > 2.0 μg/mL (P = 0.02). There was no statistically significant difference between patients with PE and without, according to age, gender and comorbidities (P > 0.05). Immobility and obesity were significantly higher among PE patients, P = 0.032 and P < 0.0001 respectively. Conclusion: AECOPD associated with pleuritic chest pain, immobility, high DD, should be considered for PE. Chest-ultrasound, as a low-cost and safe procedure, can be a very helpful investigation.
Keywords: COPD; D-dimer; pulmonary embolism; deep vein thrombosis; chest ultrasonography; lung computed tomography angiography